THE EFFECT OF LEADERSHIP STYLE AND COMMUNICATION ON EMPLOYEE PERFORMANCE - Ferdinandus Sampe; Diding Kusnady; Dede Supendi (SEAN Institute, 2023)
Creating conditions for good governance is the dream of every Regional Apparatus Organization (OPD), including the Public Works and Spatial Planning Office of Bandung Regency. However, to make this happen, support from qualified human resources is needed to be able to produce better organizational performance. Organizational performance can be achieved with the condition that high employee performance is the prime mover in the Regional Apparatus Organization or other organizations. The increase in employee performance is thought to be influenced by leadership and communication styles. Thus, the purpose of this study was to determine and explain whether leadership and communication styles have a partial and simultaneous effect on employee performance. The population used was all employees of the Bandung Regency Public Works and Spatial Planning Office, with a sample of 100 people. The analytical tool used is multiple linear regression analysis. The results of partial and simultaneous analysis show that leadership and communication styles have an effect on improving employee performance at the Public Works and Spatial Planning Office of Bandung Regency.